2015
DOI: 10.1302/0301-620x.97b5.33940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the foot and ankle outcome score in patients with osteoarthritis of the ankle

Abstract: The foot and ankle outcome score (FAOS) has been evaluated for many conditions of the foot and ankle. We evaluated its construct validity in 136 patients with osteoarthritis of the ankle, its content validity in 37 patients and its responsiveness in 39. Data were collected prospectively from the registry of patients at our institution. All FAOS subscales were rated relevant by patients. The Pain, Activities of Daily Living, and Quality of Life subscales showed good correlation with the Physical Component score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 38 publications
2
57
0
1
Order By: Relevance
“…We used foot and ankle outcome scores (FAOSs) [25], which included subscores (score, 0-100; subscales: pain, symptoms, ADLs, sports and recreation [Sports/Rec], and quality of life [QoL]) and total scores (score 0-500) to assess clinical outcomes. Ankle pain was evaluated using the visual analog scale (VAS) (from 0 to 10).…”
Section: Assessing Clinical Outcomes and Measurement Parametersmentioning
confidence: 99%
“…We used foot and ankle outcome scores (FAOSs) [25], which included subscores (score, 0-100; subscales: pain, symptoms, ADLs, sports and recreation [Sports/Rec], and quality of life [QoL]) and total scores (score 0-500) to assess clinical outcomes. Ankle pain was evaluated using the visual analog scale (VAS) (from 0 to 10).…”
Section: Assessing Clinical Outcomes and Measurement Parametersmentioning
confidence: 99%
“…All patients were followed up at two weeks, six weeks, three months, six months, at one year and yearly thereafter. At the latest follow-up, modified American Orthopaedic Foot and Ankle Society (AOFAS) 24 , Foot and Ankle Outcome Scores (FAOS) 25 and EuroQol-5 dimension (EQ-5D) 26 scores were collected, along with weight-bearing radiographs of the ankle.…”
Section: This Is a Singlementioning
confidence: 99%
“…In the original study , no floor effects were observed, although ceiling effects were evident for the pain (34% of patients recording the highest possible score), other symptoms (24%), activities of daily living (44%), sport and recreation (30%), and quality of life (19%) subscales. Ceiling effects were also observed in a study of 136 patients undergoing surgery for ankle osteoarthritis, in which 29% of patients recorded the highest possible score for the sport and recreation subscale .…”
Section: Foot and Ankle Outcome Scorementioning
confidence: 80%